2021
DOI: 10.1007/s40653-021-00392-8
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Events and Adolescent Psychopathology: A Person-Centred Approach to Expanding Adverse Childhood Experience Categories

Abstract: Stress from cumulative adverse childhood experiences (ACEs) can pose a serious risk of experiencing anxiety, depression, and other mood disorders in adolescence. However, there is a paucity of research identifying specific profiles or combinations of exposure to other forms of stressful life events and their impact on adolescent psychopathology. This study attempted a conceptual expansion of the ACE checklist by examining these stressful events. The study used cross-sectional data from a modified version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 74 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…Wang, Yu, et al, 2022;Xiao et al, 2023;Yuan et al, 2022;Zietz et al, 2020), the Childhood Trauma Questionnaire (S. S. Chen, He, et al, 2022;M. Chen, Tian, et al, 2022;Lee et al, 2021;Li et al, 2022;Shin et al, 2018;Turner et al, 2021), Children of Alcoholic Screening Test (Shin et al, 2018), the Conflict Tactic Scale (Brown et al, 2019;Lee et al, 2021;Tynan et al, 2022), the Stressful Life Events Checklist (MacLochlainn et al, 2022), Positive Achievement Change Tool (Wolff et al, 2018), and Juvenile Victimization Questionnaire (Grummitt et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang, Yu, et al, 2022;Xiao et al, 2023;Yuan et al, 2022;Zietz et al, 2020), the Childhood Trauma Questionnaire (S. S. Chen, He, et al, 2022;M. Chen, Tian, et al, 2022;Lee et al, 2021;Li et al, 2022;Shin et al, 2018;Turner et al, 2021), Children of Alcoholic Screening Test (Shin et al, 2018), the Conflict Tactic Scale (Brown et al, 2019;Lee et al, 2021;Tynan et al, 2022), the Stressful Life Events Checklist (MacLochlainn et al, 2022), Positive Achievement Change Tool (Wolff et al, 2018), and Juvenile Victimization Questionnaire (Grummitt et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, physical disability was also regarded as an ACE (G. F. Wang, Yuan, et al, 2022;Zhang et al, 2020). Further, individuals' involvement with the criminal justice system was presented as the following ACEs: "Trouble with police" (MacLochlainn et al, 2022;Ross et al, 2022), "arrested," "convicted for a crime," and "probation" (Heidinger & Willson, 2022).…”
Section: Indicatorsmentioning
confidence: 99%
“…Being male or female has long been seen as an important variable when considering relationships with peers. Girls are considered to be more oriented toward other peers [ 65 ], they show higher-quality relationships than males [ 66 ], better peer communication [ 67 ] and their relationships are often more characterized by prosocial behaviour [ 68 , 69 ]. Other studies have, however, suggested that they are less socially connected with their classmates than boys [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have, however, suggested that they are less socially connected with their classmates than boys [ 30 ]. In addition, they claim to have more stressful events in their relationships with peers [ 29 , 65 , 68 ], and they appear to be more vulnerable when their peer connections end [ 70 ]. Male peer relationships seem to be characterized by a larger size of the group and a greater number of connections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with existing research on the topic, these findings focused on adverse experiences related to the familial environment. Yet, a recent NI based study calls for the expansion of the ACE checklist to include stressful events in other settings (MacLochlainn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%